المبادئ الإسلامية في حكاية ملوك باساي وعلاقتها بالواقع المعاصر: Islamic Perspective in ‘Hikayat Raja-Raja Pasai’ and its Relevance in the Contemporary Muslim World - Shariffudin , Siti Hajar; Ahmad H. Osman, Rahmah; Majlan, Nurul Shahirah; Mohd Yazid, Naurah Hanani (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
ملخص يعود تاريخ حكاية ملوك باساي إلى القرن الخامس عشر في نوسانتارا، ويعتبر تاريخ ملوك باساي أقدم كتاب ماليزي مكتوب يمكن استرجاعه ويحتوي على عناصر إسلامية أو عربية في كتابته. وقد كتبت هذه الحكاية في الأصل بالخط الجاوي، وغالبا ما استخدمه المؤرخون كمعيار لظهور الإسلام في عالم الملايو. إن الطبيعة الإسلامية في حكاية ملوك باساي تدل على وجود الإسلام في ذلك الوقت، مع سيطرة الحكام المسلمين على ممالكهم باستخدام القوانين الإسلامية ودمج المكونات الإسلامية في تقاليدهم وعاداتهم التي تمارس في ذلك الزمان. هذه الحكاية أيضا تناول النصوص والقضايا التي أثيرت داخل المحاكم والتي من المشوق تحليلها. وعلى الرغم من أن حكاية ملوك باساي غالبا ترتبط بمسؤوليتها التاريخية، فإن هذه الورقة تقدم زاوية جديدة في عرض التاريخ القديم من خلال إظهار علاقته بعد ستة قرون مع أحوال العالم الإسلامي المعاصر باستخدام المنهج التحليلي والوصفي. وتهدف هذه المقالة للتعريف بحكاية ملوك باساي والكشف عن المبادئ الإسلامية فيها وكذلك بيان مخالفتها للمباديء الإسلامية في بعض الجوانب مع توضيح علاقتها بالمواقع المعاصر. Abstract Dating back to the 15th century Nusantara, Hikayat Raja-Raja Pasai was known as the earliest retrievable written Malay scripture that contains Islamic or Arabized elements in its penning. This scripture which was originally written in Jawi writing, often used by the historians as an indication for the coming of Islam in the Malay World. The Islamized nature of Hikayat Raja-Raja Pasai reflects the position of Islam at that time, with Muslim rulers reigning over their kingdoms using Islamic laws and incorporate Islamic components in their traditions and customs practiced within their timeframe. The text also captured the issues erupted within the courts which is interesting to analyse. Although Hikayat Raja-Raja Pasai is often associated with its historical accountability, this article offers a new angle in viewing the ancient chronicle by reflecting its relevance six centuries later with the conditions of the contemporary Muslim world by using analytical research. This article aims to dig about the Pasai kings from the book and list the Islamic principles and what contradicts them with the contemporary world nowadays. The result has found that there is a lot of Islamic influence in and also what contradicts it, this story, although it is ancient and can relate some of them with the world today.